ANALISIS KEBUTUHAN BAHAN BAKU KAYU BULAT PADA INDUSTRI KAYU LAPIS PT. KATINGAN TIMBER CELEBES - . Makkarennu; Beta Putranto; M. Daniel Dessaratu (Forestry Faculty of Universitas Hasanuddin, 2010)
The aim of this research was to predict the amounts of raw materials needed by industry for the next years. This study was conducted at the plywood industry in PT.Katingan Timber Celebes. For the purpose of the study, utilisation of raw material for five years (2004-2008) were collected. The obtained data were analyzed by using regresi with time series data. It is predicted that the amount of raw material for the industry (2009) will be 166,758.2 m3 consisting of meranti (130,699.4 m3) and rimba campuran (36,053.8 m3) Key words: prediction, plywood industry, utilisation of raw material